Dry vs. wet ad libitum feeding of finishing swine - J Vargas Vargas; Robert H Hines (Kansas Agricultural Experiment Station Research Reports, 1985)
Two hundred finishing pigs were used to evaluate wet vs. dryad libitum feeding. Growth rate of finishing pigs was significantly improved (5%) by wet feeding. Feed utilization was improved 4.5% by wet feeding. Dry feeder type did not influence performance, since all pigs fed dry diets performed similarly. Likewise, pigs fed wet diets performed equally regardless of wet feeder type.; Swine Day, Manhattan, KS, November 21, 1985
Keywords: Swine day; 1985; Kansas Agricultural Experiment Station contribution; no. 86-145-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 486; Swine; Wet vs. dry ad libitum; Finishing pigs; Growth rate